The Effect of Investment Decisions & Dividend Policies on The Value of Companies In The Industrial Goods Sub-Sector - Iskandar, Zeinku Putri; Asih, Vemy Suci; Nurjaman, Ilham; Kusuma, Suteja Wira Dana (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Firm value and share price are closely related. A high stock price indicates a strong company value in the capital market. The Industrial Goods sub-sector is a sector that provides capital to be used in the production process in various industries, in the form of machinery, equipment and equipment for manufacturing, construction and goods and services. This study aims to determine whether investment decisions represented by the Price Earning Ratio (PER) and dividend policy represented by the Dividend Payment Ratio (DPR) affect firm value represented by Price per Book Value (PBV) in industrial goods sub-sector companies for the period 2019 to 2023 which are officially listed on the IDX. The associative method with a quantitative approach was used in this study, with a sample size of six companies out of 40 companies with a period of 5 years. It was found in this study that PER as a proxy for investment decisions contributed positively to increasing firm value as measured by PBV but was not significant. Meanwhile, Dividend Payment Ratio (DPR) as a representation of dividend policy significantly and positively affects Price Book Value (PBV) as a representation of firm value.